Pelatihan Aplikasi SDKI SLKI SIKI di RS PKU Muhammadiyah Karangnyar - Yuli Widyastuti; Heni Purwaningsih; Nurul Istiqomah; Anis Prabowo; Cemy Nur Fitria (Lembaga Pengembangan Kinerja Dosen, 2024)
The Indonesian Nursing Diagnosis Standard (SDKI), Indonesian Nursing Outcome Standard (SLKI), and Indonesian Nursing Intervention Standard (SIKI) are standardized nursing documentation systems designed to improve the quality of nursing care. The training on the application of SDKI, SLKI, and SIKI at PKU Muhammadiyah Karanganyar Hospital aims to enhance nurses' understanding and skills in systematically, accurately, and evidence-based nursing documentation. The training methods included lectures, discussions, and hands-on practice in applying SDKI, SLKI, and SIKI to real cases. Evaluation results showed a significant improvement in participants' understanding and skills after completing the training. The implementation of SDKI, SLKI, and SIKI is expected to enhance nursing documentation efficiency and improve the quality of nursing services in the hospital.